Category characteristics of high school students’ sense of hope and its relationship with mental health - Wang, Rui; Di, Siyu; Sun, Yajing; Liu, Yafei; Ma, Chao (Frontiers in Psychology, 2023)
Purpose This study used the latent profile analysis technique to investigate the latent categories of high school students’ sense of hope and their relationship with mental health. Methods A total of 1,513 high school students from six middle schools in China was tested using the Adult Dispositional Hope Scale and the Symptom Checklist 90. Analysis of variance was used to explore the relationship between latent categories of sense of hope and mental health. Results High school students’ sense of hope scores are negatively associated with mental health scores. The high school students’ sense of hope could be divided into three latent categories: negative sense of hope group, moderate sense of hope group and positive sense of hope group. The differences in scores on each dimension of mental health among high school students with different latent categories of sense of hope were statistically significant. The positive sense of hope group had lower scores on the dimensions of somatization, compulsive symptoms, interpersonal sensitivity, depression, anxiety, hostility, terror, paranoia, and psychosis than the negative sense of hope group and the moderate sense of hope group. Conclusion There are three latent categories of high school students’ sense of hope, and the sense of hope category is closely related to mental health. Based on the different categories of high school students’ sense of hope, the program of mental health education can be reasonably selected to create a positive general environment for mental health education and ultimately enhance the mental health of high school students.